Does angulation of osteotome during pterygomaxillary dysjunction for a Le Fort I osteotomy influence stress transmission to the orbit? A finite element simulation in normal and cleft maxillae. Issue 4 (May 2021) - Juliet, M.; Parameswaran, A.; Pedamally, M.; Aggarwal, N.; Ramanthan, M.; Mori, Y.
Abstract: Pterygomaxillary (PTM) dysjunction is a technique-sensitive step in Le Fort I osteotomy. Various studies implicate improper osteotomy techniques and anatomical variations of the midface in ophthalmic/orbital complications. The aim of this study was to assess the stress distribution and its transmission to the orbit during PTM dysjunction while using different angulations of the osteotome. The study involved the generation of two virtual models from the computed tomographic images of a non-cleft and cleft patient. Nonlinear, three-dimensional finite element analysis (3D-FEA) of the models was performed for mapping the equivalent stress (in megapascals [MPa]) and maximum principal stress (in MPa) at the PTM junction, optic canal, and superior orbital fissures. The results of our study showed that there was no significant change in the transmission of stress to the bony orbit in a normal maxilla, with variations in the angulation of the osteotome. However, the equivalent stress generated for the cleft maxilla showed an increase that could potentiate indirect globe injury. The study shows that a judicious technique for PTM dysjunction and a cautious approach in cleft maxillae could reduce incidence of ophthalmic complications in clinical practice.